Managing CCTV in Indonesian Hospitals: A Legal, Ethical, and Managerial Perspective - Sarwono, Aditya Pratama (Universitas Muhammadiyah Yogyakarta, 2024)
Closed Circuit Television (CCTV) in Indonesian hospitals presents significant legal, ethical, and managerial challenges, particularly due to unclear regulations governing its installation in clinic rooms. The absence of specific guidelines raises legal uncertainties, casting doubt on patient privacy and the hospital's responsibility for safeguarding sensitive medical information. Ethical concerns intensify as the use of CCTV in clinic rooms may lead to potential privacy violations in the absence of clear regulations. This condition certainly poses managerial challenges for hospitals, affecting resource allocation, personnel training, and the management of data related to the CCTV system. Effectively managing this system becomes crucial to balance surveillance needs with privacy protection. Hence, this research aims to explore legal uncertainties surrounding CCTV installation, identify ethical issues, and evaluate managerial impacts. The study seeks to offer profound insights, aiding the development of pertinent policies, ethical frameworks, and effective managerial strategies for a balanced and responsible CCTV implementation in healthcare settings.